Method for predicting battery capacity based on W18O49 color change

By introducing a W18O49 layer modified with carbon quantum dots into the positive electrode of the battery, using its electrochromic characteristics, the accurate prediction of battery capacity is achieved, the problem of inaccurate battery capacity evaluation in the prior art is solved, and the battery recycling efficiency and environmental protection effect are improved.

CN119881698AActive Publication Date: 2025-04-25KUNMING UNIV OF SCI & TECH
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510098718.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-22
Publication Date
2025-04-25
Estimated Expiration
2045-01-22

AI Technical Summary

Technical Problem

The prior art is difficult to accurately evaluate battery capacity, resulting in low battery scrap recycling efficiency, affecting resource conservation and environmental protection.

Method used

By introducing a W18O49 layer modified by carbon quantum dots at the positive electrode of the battery, using its electrochromic properties, the color of W18O49 changes irreversibly as the battery capacity decays, achieving accurate prediction of the battery capacity.

Benefits of technology

It realizes accurate prediction of battery capacity, avoids unnecessary battery scrapping and resource waste, and improves battery recycling efficiency and environmental protection effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005253588340000011
    Figure HDA0005253588340000011
  • Figure HDA0005253588340000012
    Figure HDA0005253588340000012
  • Figure HDA0005253588340000013
    Figure HDA0005253588340000013
Patent Text Reader

Abstract

The invention relates to a method for predicting battery capacity based on W18O49 color change, and belongs to the technical field of battery manufacturing. A carbon quantum dot modified W18O49 loaded conductive fiber substrate is used as a visual electrode for detecting the capacity of an intelligent battery, an alkali metal foil is used as a battery negative electrode, a transparent PET, PC, PMMA or PVA shell is used as a shell, a flexible energy storage battery device with the visual capacity is constructed, the initial color value of a W18O49 layer of a positive electrode of the intelligent battery is detected as a standard color value, and the capacity of the intelligent battery is detected. Carrying out charge and discharge detection on the battery, synchronously detecting color values of the battery positive electrode W18O49 layers when the battery capacities are different, calculating color values of the color values of the battery positive electrode W18O49 layers with the different battery capacities relative to a standard color value, and drawing a battery capacity-color difference value standard curve; detecting the actual color value of the positive electrode W18O49 layer of the intelligent battery to be predicted, calculating the actual color difference value of the actual color value relative to the standard color value, and predicting the actual capacity of the intelligent battery according to the actual color value and the battery capacity-color difference value standard curve so as to quantitatively determine the battery capacity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method based on W 18 O 49 The invention relates to a method for predicting battery capacity by color change, and belongs to the technical field of battery manufacturing. Background Art

[0002] Accurately assessing battery capacity has always been an urgent problem to be solved in the field of energy storage. This is not only related to the user's travel experience, but also to the scrapping and recycling of batteries. Timely grasping the remaining battery power can not only give users a reminder that they need to replace new batteries, but also to the recycling of batteries, which is crucial to achieving resource conservation and alleviating environmental problems. However, it is often difficult to assess the remaining battery power and whether it has reached the standard of failure and scrapping. Since batteries are usually opaque packages, the macroscopic assessment of the entire internal power is like a "black box". The current technology is also limited to indirect comprehensive analysis of the current (I), voltage (V), impedance (R) and temperature (T) during the operation of single or module batteries to define whether it has reached failure and scrapping. Therefore, it is of great significance to develop a detection device that can accurately assess the remaining capacity of the battery. Several directions that have been studied are not yet mature. Some researchers have tried to introduce sensors inside the battery, which not only consumes additional energy, but also introduces additional devices and increases costs. Other researchers have introduced artificial intelligence big data calculation methods to predict battery failure. They have tried to establish a capacity failure model and improve the accuracy of prediction by feeding data. However, these methods are still immature. The accuracy of the model and the impact of temperature, environment, etc. on battery data all pose considerable difficulties for machine learning research. Summary of the invention

[0003] In view of the existing technical problems that it is difficult and inaccurate to accurately evaluate the battery capacity, the present invention proposes a method based on W 18 O 49 Color change prediction method for battery capacity, using W 18 O 49 The electrochromic properties of W 18 O 49 Modification is then performed on the carbon quantum dot-modified W 18 O 49 By introducing the positive electrode of the battery, a smart battery capable of evaluating the battery capacity is prepared. The smart battery can directly observe the W 18 O 49 The capacity of the battery is detected by the change of 18 O 49 The color of W undergoes a corresponding irreversible change. 18 O 49The irreversible color change of corresponds to the attenuation mechanism of the battery capacity, which is the irreversible embedding of alkali metal ions leading to the collapse of the microstructure. 18 O 49 The electrochromic effect and the ability to store ions decay synchronously, enabling accurate prediction of the remaining capacity of the battery.

[0004] A W-based 18 O 49 The method for predicting battery capacity by color change, the specific steps are as follows:

[0005] (1) The conductive fiber treated with concentrated acid for 1 to 3 hours was used as the substrate template. The substrate template was in situ reacted in WCl3 ethanol solution to self-grow W 18 O 49 layer;

[0006] (2) In situ growth of W 18 O 49 The conductive fiber of the layer is used as the working electrode, the Pt electrode is used as the counter electrode, and the Ag / AgCl electrode is used as the reference electrode. Carbon quantum dots are electrodeposited in the carbon quantum dot solution to obtain carbon quantum dot-modified W 18 O 49 layer, and then annealed at 100-500℃ for 1-8h to obtain W 18 O 49 Color electrode;

[0007] (3) With W 18 O 49 The color-developing electrode is the positive electrode of the battery, the alkali metal foil is the negative electrode of the battery, the transparent PET, PC, PMMA or PVA shell is the outer shell, the alkali metal salt / organic solution system, the zinc salt / organic solution system, the alkali metal salt / aqueous solution system or the zinc salt / aqueous solution system is the electrolyte, and PE, PP or cellulose is the diaphragm. The positive electrode of the battery, the negative electrode of the battery, the electrolyte, the diaphragm and the outer shell are assembled into a smart battery; the electrolytes are all conventional commercially available electrolytes or prepared according to conventional electrolyte concentrations;

[0008] (4) Detect when the smart battery is fully charged. 18 O 49 The initial color value of the layer is used as the standard color value to perform charge and discharge detection on the battery. When the battery is fully charged, the capacity decays. When the battery is fully charged, the capacity decay process corresponding to the positive electrode W of the battery with different full-charge capacities is also detected simultaneously. 18 O 49 The color value of the layer is detected by the colorimeter, and the positive electrode W of the battery at different full battery capacities is 18 O 49 The color difference value of the layer relative to the standard color value is used to draw a battery capacity-color difference value standard curve;

[0009] (5) Detect the positive electrode W when the predicted smart battery is fully charged 18 O 49 The actual color value of the layer is measured, and the actual color difference value of the actual color value relative to the standard color value is detected by a colorimeter. According to the actual color difference value and the battery capacity-color difference value standard curve, the actual capacity of the fully charged smart battery is predicted.

[0010] Preferably, the conductive fiber in step (1) is conductive carbon fiber, conductive silver fiber, conductive copper fiber, conductive platinum fiber or conductive nickel fiber, and the concentrated acid is concentrated nitric acid, concentrated nitric acid or concentrated hydrochloric acid.

[0011] Preferably, the mass concentration of concentrated nitric acid is 30-65%, the mass concentration of concentrated sulfuric acid is 50-98%, and the mass concentration of concentrated hydrochloric acid is 12-36.5%.

[0012] Preferably, the mass concentration of the WCl3 ethanol solution in step (1) is 5-50%, the in-situ reaction temperature is 120-180°C, and the reaction time is 2-24h.

[0013] Preferably, in step (2), the concentration of the carbon quantum dot solution is 0.01 to 0.05 mol / L, the electrodeposition voltage is -3.7 to 3.7 V, and the time is 0.5 to 2 h.

[0014] Preferably, the alkali metal foil in step (3) is lithium foil, sodium foil, potassium foil or zinc foil.

[0015] Preferably, the alkali metal salt in step (3) is lithium hexafluorophosphate (LiPF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium tetrafluoroborate (LiBF4), sodium hexafluorophosphate (NaPF6), sodium tetrafluoroborate (NaBF4), sodium bis(fluorosulfonyl)imide (NaFSI) KPF6, KFSI (potassium bis(trifluoromethanesulfonyl)imide) or KTFSI (potassium bis(trifluoromethanesulfonyl)imide), and the zinc salt is ZnSO4.

[0016] Preferably, the standard color values ​​of step (4) are: L*=20-60, a=0-20, b=-60.0-0 (Lab mode).

[0017] The beneficial effects of the present invention are:

[0018] (1)W 18 O 49 The carbon quantum dots were self-grown on the conductive fibers and modified on the W by electrodeposition. 18 O 49The surface is annealed, and the initial color can be stabilized to blue (the absorption spectrum wavelength range is adjustable between 360-560nm) by quantitatively controlling the modification amount of carbon quantum dots. The battery is then packaged: a transparent shell is used as the battery shell, and alkali metals are used as counter electrodes to provide free-moving cations to construct a flexible, transparent, visual smart battery. This battery can be used as a W-based 18 O 49 Energy storage devices whose color changes predict battery capacity;

[0019] (2) In the present invention, as the capacity of the smart battery decays, W 18 O 49 The color of W undergoes a corresponding irreversible change. 18 O 49 The irreversible color change corresponds to the attenuation mechanism of the battery capacity, which is the irreversible embedding of alkali metal ions leading to the collapse of the microstructure. 18 O 49 The electrochromic effect and the ability to store ions decay synchronously, enabling accurate prediction of the remaining capacity of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 is W of Example 1 18 O 49 XRD pattern of

[0021] Figure 2 is the W annealed at different temperatures in Example 1 18 O 49 Optical microscope photo of the color-developing electrode;

[0022] Figure 3 This is a schematic diagram of the structure of a visual smart battery according to the present invention;

[0023] Figure 4 The standard curve of lithium ion battery capacity-color difference value in Example 1;

[0024] Figure 5 The discharge curves of four visualized smart sodium-ion batteries assembled in Example 2;

[0025] Figure 6 The sodium ion battery capacity-color difference value standard curve of Example 2;

[0026] Figure 7 The gradually changing electrode color reflectivity curve under different charge and discharge times in Example 2;

[0027] Figure 8 The following are photos of the color changes of the electrodes at different charge and discharge times in Example 2;

[0028] Fig. 9The standard control curve of potassium ion battery capacity-color difference value in Example 3;

[0029] Fig.10 This is the standard control curve of zinc ion battery capacity-color difference value in Example 4. DETAILED DESCRIPTION

[0030] The present invention is further described in detail below in conjunction with specific implementation modes, but the protection scope of the present invention is not limited to the described contents.

[0031] Embodiment 1: A method based on W 18 O 49 The method for predicting battery capacity by color change, the specific steps are as follows:

[0032] (1) The conductive fiber soaked in 65% concentrated nitric acid for 2 h was used as the substrate template. The substrate template was in situ reacted in 15% WCl3 ethanol solution for 3 h to self-grow W 18 O 49 layer;

[0033] (2) In situ growth of W 18 O 49 The conductive fiber of the layer was used as the working electrode, the Pt electrode was used as the counter electrode, and the Ag / AgCl electrode was used as the reference electrode. In a carbon quantum dot solution with a concentration of 0.05 mol / L, carbon quantum dots were electrodeposited at a voltage of -0.8 V for 0.5 h to obtain W modified with carbon quantum dots. 18 O 49 layer, and then annealed at 200℃ and 2h to obtain W 18 O 49 Color electrode;

[0034] In this embodiment, W 18 O 49 Layer and 200℃ annealing treatment W 18 O 49 The XRD pattern of Figure 1 ,from Figure 1 It can be seen that the self-grown material is W 18 O 49 , and no phase change occurs after annealing;

[0035] In this embodiment, W annealed at different temperatures 18 O 49 Optical microscope photos of the color-developing electrode are shown in Figure 2 ,from Figure 2 It can be seen that after quantum dot modification, W 18 O 49 W obtained by annealing the layer at different temperatures 18 O 49The initial colors of the color-developing electrodes are consistent, and the wavelengths of the reflection spectra are 460.4nm, 458.8nm, 460.2nm, and 460.1nm, respectively, with a wavelength error of less than 0.05%;

[0036] (3) With W 18 O 49 The color-developing electrode is the positive electrode of the battery, the Li foil is the negative electrode of the battery, the transparent PET shell is the outer shell, the lithium hexafluorophosphate dissolved in EC / DM=1:1 is used as the electrolyte, and PE is used as the diaphragm. The positive electrode, the negative electrode, the electrolyte, the diaphragm, and the outer shell are assembled into a smart lithium-ion battery (see Figure 3 );

[0037] (4) Detect the positive electrode W when the smart lithium-ion battery is fully charged 18 O 49 The initial color value of the layer is used as the standard color value (standard color value: L*=55.0, a=15.0, b=-25.0 (Lab mode)), and the battery is charged and discharged to detect the capacity decay of the battery when it is fully charged, and the battery positive electrode W corresponding to the full charge capacity of different lithium-ion batteries in the process of capacity decay when the battery is fully charged is detected simultaneously. 18 O 49 The color value of the layer is detected by the colorimeter, and the positive electrode W of the battery with different full-charge capacity is detected 18 O 49 The color difference value of the layer relative to the standard color value is used to draw a battery capacity-color difference value standard curve (see Figure 4 );

[0038] (5) Detect the positive electrode W of the battery when the intelligent lithium-ion battery is fully charged. 18 O 49 The actual color value of the layer (L*=25.0, a=5.0, b=-5.0) is detected by a colorimeter to obtain an actual color difference value (52) of the actual color value relative to the standard color value, and the actual capacity of the fully charged smart lithium-ion battery is predicted based on the actual color difference value and a battery capacity-color difference value standard curve;

[0039] In this embodiment, the actual capacity of the smart battery to be predicted is 5000 mAh.

[0040] Embodiment 2: A method based on W 18 O 49 The method for predicting battery capacity by color change, the specific steps are as follows:

[0041] (1) The conductive fiber that had been soaked in 36.5% concentrated hydrochloric acid for 3 h was used as the substrate template. The substrate template was in situ reacted in 15% WCl3 ethanol solution for 2 h to self-grow W 18 O 49 layer;

[0042] (2) In situ growth of W 18 O 49 The conductive fiber of the layer was used as the working electrode, the Pt electrode was used as the counter electrode, and the Ag / AgCl electrode was used as the reference electrode. In a carbon quantum dot solution with a concentration of 0.05 mol / L, carbon quantum dots were electrodeposited at a voltage of -3.7 V for 2 h to obtain carbon quantum dot-modified W 18 O 49 layer, and then annealed at 200℃ for 2h to obtain W 18 O 49 Color electrode;

[0043] (3) With W 18 O 49 The color-developing electrode is the positive electrode of the battery, the Na foil is the negative electrode of the battery, the transparent PMMA shell is the outer shell, the sodium perchlorate dissolved in ethylene carbonate and dimethyl carbonate is the electrolyte, and the cellulose is the separator. The positive electrode, the negative electrode, the electrolyte, the separator, and the outer shell are assembled into 4 smart sodium-ion batteries (see Figure 3 );

[0044] The discharge curves of the four visualized intelligent sodium ion batteries in this embodiment are shown in Figure 5 ,from Figure 5 It can be seen that the capacities of the four visualized intelligent sodium-ion battery discharge curves are almost the same, proving the consistency of the capacities of different batches, and the error of discharge capacity of different batches is less than 0.5%;

[0045] (4) Detect the positive electrode W when the smart sodium-ion battery is fully charged 18 O 49 The initial color value of the layer is used as the standard color value (standard color value: L*=44.0, a=15.0, b=-33.0 (Lab mode)), and the battery is charged and discharged to detect the capacity decay of the battery when it is fully charged, and the battery positive electrode W corresponding to the full charge capacity of different sodium ion batteries in the process of capacity decay when the battery is fully charged is synchronously detected. 18 O 49 The color value of the layer is detected by the colorimeter, and the positive electrode W of the battery with different full-charge capacity is detected 18 O 49 The color difference value of the layer relative to the standard color value is used to draw a battery capacity-color difference value standard curve (see Figure 6 );

[0046] The gradient electrode color reflectivity curve under different charge and discharge times is shown in Figure 7 , the actual photos of the corresponding electrode color changes under different charge and discharge times are shown in Figure 8 ,from Figures 7-8 It can be seen that as the number of cycles increases, the color gradually becomes darker and the wavelength moves from 340 to the left;

[0047] (5) Detect the positive electrode W of the smart sodium ion battery to be predicted 18 O 49 The actual color value of the layer (L*=14.0, a=2.0, b=-3.0) is obtained, and the actual color difference value (58) of the actual color value relative to the standard color value is detected by a colorimeter, and the actual capacity of the fully charged smart sodium-ion battery is predicted according to the actual color difference value and the battery capacity-color difference value standard curve;

[0048] The actual capacity of the smart battery to be predicted in this embodiment is 3000 mAh.

[0049] Embodiment 3: A method based on W 18 O 49 The method for predicting battery capacity by color change, the specific steps are as follows:

[0050] (1) The conductive fiber soaked in 98% concentrated sulfuric acid for 1 h was used as the substrate template. The substrate template was in situ reacted in 20% WCl3 ethanol solution for 3 h to self-grow W 18 O 49 layer;

[0051] (2) In situ growth of W 18 O 49 The conductive fiber of the layer was used as the working electrode, the Pt electrode was used as the counter electrode, and the Ag / AgCl electrode was used as the reference electrode. In a carbon quantum dot solution with a concentration of 0.04 mol / L, carbon quantum dots were electrodeposited at a voltage of 3.7 V for 3 h to obtain carbon quantum dot-modified W 18 O 49 layer, and then annealed at 300℃ for 2h to obtain W 18 O 49 Color electrode;

[0052] (3) With W 18 O 49 The color-developing electrode is the positive electrode of the battery, the K foil is the negative electrode of the battery, the transparent PC shell is the outer shell, KFSI (potassium bis(fluorosulfonyl)imide) is the electrolyte, and PP is the diaphragm. The positive electrode, the negative electrode, the electrolyte, the diaphragm, and the outer shell are assembled into an intelligent potassium ion battery (see Figure 3 );

[0053] (4) Detect the positive electrode W when the smart sodium-ion battery is fully charged 18 O 49 The initial color value of the layer is used as the standard color value (standard color value: L*=42.0, a=10.0, b=-36.0 (Lab mode)), and the battery is charged and discharged to detect the capacity decay of the battery when it is fully charged, and the battery positive electrode W corresponding to the full charge capacity of different sodium ion batteries in the process of capacity decay when the battery is fully charged is synchronously detected. 18 O 49The color value of the layer is detected by the colorimeter, and the positive electrode W of the battery with different full-charge capacity is detected 18 O 49 The color difference value of the layer relative to the standard color value is used to draw a battery capacity-color difference value standard curve (see Fig. 9 );

[0054] (5) Detect the positive electrode W of the smart sodium ion battery to be predicted 18 O 49 The actual color value of the layer (L*=9.0, a=5.0, b=-7.0) is obtained, and the actual color difference value (52) of the actual color value relative to the standard color value is detected by a colorimeter, and the actual capacity of the fully charged smart sodium-ion battery is predicted according to the actual color difference value and the battery capacity-color difference value standard curve;

[0055] The actual capacity of the smart battery to be predicted in this embodiment is 4000 mAh.

[0056] Embodiment 4: A method based on W 18 O 49 The method for predicting battery capacity by color change, the specific steps are as follows:

[0057] (1) The conductive fiber soaked in 98% concentrated sulfuric acid for 2 h was used as the substrate template. The substrate template was in situ reacted in 30% WCl3 ethanol solution for 1 h to self-grow W 18 O 49 layer;

[0058] (2) In situ growth of W 18 O 49 The conductive fiber of the layer was used as the working electrode, the Pt electrode was used as the counter electrode, and the Ag / AgCl electrode was used as the reference electrode. In a carbon quantum dot solution with a concentration of 0.05 mol / L, carbon quantum dots were electrodeposited at a voltage of -1.0 V for 1 h to obtain carbon quantum dot-modified W 18 O 49 layer, and then annealed at 250°C for 1.5h to obtain W 18 O 49 Color electrode;

[0059] (3) With W 18 O 49 The color-developing electrode is the positive electrode of the battery, the Zn foil is the negative electrode of the battery, the transparent PC shell is the outer shell, 1 mol / L ZnSO4 aqueous solution is used as the electrolyte, and glass cellulose is used as the diaphragm. The positive electrode, the negative electrode, the electrolyte, the diaphragm, and the outer shell are assembled into an intelligent zinc ion battery (see Figure 3 );

[0060] (4) Detect the positive electrode W when the smart zinc-ion battery is fully charged 18 O 49The initial color value of the layer is used as the standard color value (standard color value: L*=43.0, a=12.0, b=-33.0 (Lab mode)), and the battery is charged and discharged to detect the capacity decay of the battery when it is fully charged, and the battery positive electrode W corresponding to the full charge capacity of different zinc ion batteries in the process of capacity decay when the battery is fully charged is synchronously detected. 18 O 49 The color value of the layer is detected by the colorimeter, and the positive electrode W of the battery with different full-charge capacity is detected 18 O 49 The color difference value of the layer relative to the standard color value is used to draw a battery capacity-color difference value standard curve (see Fig.10 );

[0061] (5) Detect the positive electrode W of the intelligent zinc-ion battery to be predicted 18 O 49 The actual color value of the layer (L*=8.0, a=8.0, b=-3.0) is obtained, and the actual color difference value (53) of the actual color value relative to the standard color value is detected by a colorimeter, and the actual capacity of the fully charged intelligent zinc-ion battery is predicted according to the actual color difference value and the battery capacity-color difference value standard curve;

[0062] The actual capacity of the smart battery to be predicted in this embodiment is 3500 mAh.

[0063] The specific implementation modes of the present invention are described in detail above, but the present invention is not limited to the above implementation modes, and various changes can be made within the knowledge scope of ordinary technicians in this field without departing from the purpose of the present invention.

Claims

1. A W-based 18 O 49 The method for predicting battery capacity by color change is characterized in that: The specific steps are as follows: (1) The conductive fiber treated with concentrated acid for 1 to 3 hours was used as the substrate template. The substrate template was in situ reacted in WCl3 ethanol solution to self-grow W 18 O 49 layer; (2) In situ growth of W 18 O 49 The conductive fiber of the layer is used as the working electrode, the Pt electrode is used as the counter electrode, and the Ag / AgCl electrode is used as the reference electrode. Carbon quantum dots are electrodeposited in the carbon quantum dot solution to obtain carbon quantum dot-modified W 18 O 49 layer, and then annealed at 100-500℃ for 1-8h to obtain W 18 O 49 Color electrode; (3) With W 18 O 49 The color-developing electrode is the positive electrode of the battery, the alkali metal foil is the negative electrode of the battery, the transparent PET, PC, PMMA or PVA shell is the outer shell, the alkali metal salt / organic solution system, the zinc salt / organic solution system, the alkali metal salt / aqueous solution system or the zinc salt / aqueous solution system is the electrolyte, and PE, PP or cellulose is the separator. The positive electrode of the battery, the negative electrode of the battery, the electrolyte, the separator and the outer shell are assembled into a smart battery; (4) Detect when the smart battery is fully charged. 18 O 49 The initial color value of the layer is used as the standard color value to perform charge and discharge detection on the battery. When the battery is fully charged, the capacity decays. When the battery is fully charged, the capacity decay process corresponding to the positive electrode W of the battery with different full-charge capacities is also detected simultaneously. 18 O 49 The color value of the layer is detected by the colorimeter, and the positive electrode W of the battery at different full battery capacities is 18 O 49 The color difference value of the layer relative to the standard color value is used to draw a battery capacity-color difference value standard curve; (5) Detect the positive electrode W when the predicted smart battery is fully charged 18 O 49 The actual color value of the layer is measured, and the actual color difference value of the actual color value relative to the standard color value is detected by a colorimeter. According to the actual color difference value and the battery capacity-color difference value standard curve, the actual capacity of the fully charged smart battery is predicted.

2. According to claim 1, based on W 18 O 49 The method for predicting battery capacity by color change is characterized by: In step (1), the conductive fiber is conductive carbon fiber, conductive silver fiber, conductive copper fiber, conductive platinum fiber or conductive nickel fiber, and the concentrated acid is concentrated nitric acid, concentrated nitric acid or concentrated hydrochloric acid.

3. According to claim 2, based on W 18 O 49 The method for predicting battery capacity by color change is characterized by: The mass concentration of the concentrated nitric acid is 30-65%, the mass concentration of the concentrated sulfuric acid is 50-98%, and the mass concentration of the concentrated hydrochloric acid is 12-36.5%.

4. According to claim 1, based on W 18 O 49 The method for predicting battery capacity by color change is characterized by: Step (1) In step (1), the mass concentration of the WCl3 ethanol solution is 5-50%, the in-situ reaction temperature is 120-180°C, and the reaction time is 2-24h.

5. According to claim 1, based on W 18 O 49 The method for predicting battery capacity by color change is characterized by: In step (2), the concentration of the carbon quantum dot solution is 0.01 to 0.05 mol / L, the electrodeposition voltage is -3.7 to 3.7 V, and the time is 0.5 to 2 h.

6. According to claim 1, based on W 18 O 49 The method for predicting battery capacity by color change is characterized by: In step (3), the alkali metal foil is lithium foil, sodium foil, potassium foil or zinc foil.

7. According to claim 1, based on W 18 O 49 The method for predicting battery capacity by color change is characterized by: In step (3), the alkali metal salt is lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium tetrafluoroborate, sodium hexafluorophosphate, sodium tetrafluoroborate, sodium bis(fluorosulfonyl)imide, potassium bis(fluorosulfonyl)imide or potassium bis(trifluoromethanesulfonyl)imide; and the zinc salt is ZnSO4.

8. According to claim 1, based on W 18 O 49 The method for predicting battery capacity by color change is characterized by: The standard color values ​​of step (4) are: L*=20~60, a=0~20, b=-60.0~0.

Citation Information

Patent Citations

  • Small and portable battery capacity detection apparatus

    CN106980088A

  • Battery and fabrication method, charging method and application thereof

    CN107317056A

  • Visual lithium ion electrode, application and visual lithium ion battery

    CN114639830A

  • Aqueous zinc ion battery based on W18O49 positive electrode

    CN116742156A

  • Inverted Fabry-Perot cavity electrochromic battery and preparation method thereof

    CN117539098A